2022
DOI: 10.3390/diagnostics12061476
|View full text |Cite
|
Sign up to set email alerts
|

Superb Microvascular Imaging (SMI) Compared with Color Doppler Ultrasound for the Assessment of Hepatic Artery in Pediatric Liver Transplants: A Feasibility Study

Abstract: (1) Background: Despite progression in surgical techniques and immunological treatments, hepatic artery (HA) thrombosis and stenosis still develop as an early or late liver transplant (LT) complication. We aimed to compare superb microvascular imaging (SMI) with conventional Doppler imaging (CDI) in the assessment of HA in a cohort of pediatric patients undergoing follow-up ultrasound (US) for LT. (2) Methods: This prospective, observational study included 73 pediatric LT recipients (median age, 7 years; IQR, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…SMI proved to be comparable to contrastenhanced ultrasound with a higher than 90% agreement compared to the standard of reference, computed tomography angiography. Also, Collaku et al [2] investigated the role of SMI in another interesting but very selected vascular application. The authors showed the added value of the technique, coupled with conventional color Doppler, in order to enhance the visibility of the hepatic artery in pediatric patients with liver transplants.…”
Section: Papers Included In the Special Issuementioning
confidence: 99%
“…SMI proved to be comparable to contrastenhanced ultrasound with a higher than 90% agreement compared to the standard of reference, computed tomography angiography. Also, Collaku et al [2] investigated the role of SMI in another interesting but very selected vascular application. The authors showed the added value of the technique, coupled with conventional color Doppler, in order to enhance the visibility of the hepatic artery in pediatric patients with liver transplants.…”
Section: Papers Included In the Special Issuementioning
confidence: 99%
“…During the last decades, different US developments have been introduced, including elastography, contrast-enhanced US (CEUS), and novel doppler techniques[ 6 - 9 ].…”
Section: Imaging Techniquesmentioning
confidence: 99%
“…CEUS is useful for lesion detection and characterization in several clinical settings, without the use of ionizing radiations and with higher temporal resolution compared to CT or MRI[ 6 ]. It can be useful in non-oncologic, non-cirrhotic patients[ 6 , 9 ], for the assessment of incidental focal lesions, in cirrhotic patients, allowing characterization of contrast enhancement patterns of hepatocellular carcinoma (HCC) with good sensitivity and specificity[ 6 ], and in oncologic patients, providing higher sensitivity compared to the standard US for liver metastases detection and indeterminate CT or MRI lesions characterization[ 12 ]. CEUS can also be used to guide, in real-time, both focal lesions procedures[ 7 , 8 ] and locoregional ablative therapies, as well as for treatment response assessment[ 13 , 14 ].…”
Section: Imaging Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is less angle-dependent than Doppler-based flow techniques and has been shown to be especially useful in areas with simultaneous low and high blood flow. Its efficacy in detecting small vessels has been demonstrated across diverse clinical applications, including the hepatic vasculature in native and transplanted livers [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%